USING INTERACTIVE TECHNOLOGIES IN THE STUDY OF ECONOMIC SUBJECTS - Volkova, N. I. (Continuing Professional Education: Theory and Practice, 2023)
Nowadays Higher educational institutions of Ukraine that prepare future economists can not stay away from accelerated, advanced and innovative development of education and demand the conditions for development of selfidentity for life. Higher education system is designed to provide knowledge about the professional sphere of activity, its specificity, has to shape the personal quality of a specialist. A graduate of Higher School should have a strong and deep knowledge of professional thinking, have their own professional and personal attitude. For this purpose it is necessary to employ the full range of psychological, pedagogical, sociological tools that are directly contribute to solving this problem. The purpose of the article is the rationale for the use of interactive technologies in the process of economic subjects. In this paper it is proved that the use of active methods of teaching and learning of the built-in interactive learning technology will improve the quality of students, to form a new generation of professionals that are designed to carry out efficiently the modernization of the modern model of the national economy.